2016
DOI: 10.1002/cssc.201601069
|View full text |Cite
|
Sign up to set email alerts
|

Dopant‐Free Zinc Chlorophyll Aggregates as an Efficient Biocompatible Hole Transporter for Perovskite Solar Cells

Abstract: Chlorophylls (Chls) are abundant, naturally occurring pigments that play key roles in light-harvesting and electron/energy transfer in natural photosynthetic apparatus. To demonstrate the idea that Chls are suitable hole transporters, we employed two Chl derivatives, Chl-1 and Chl-2, which self-assembled readily into π-stacking aggregates through a simple spincasting process, in perovskite solar cells (PSCs). The Chl aggregate films exhibit an ultra-smooth film surface, high hole mobility, appropriate energy l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 58 publications
0
76
0
Order By: Relevance
“…DSC, as a suitable dye sensitizer, exhibits a promising photovoltaic potential, and features a carboxy group at the C3 2 position on the chlorin macrocycle for covalent bonding with the TiO 2 nanocrystalline films. Some solution‐based DSSCs based on DSC have been investigated previously . In contrast, it has been observed that HTC‐1 and HTC‐2 show efficient charge transport with high mobilities owing to the combination of π–π stacking of the chlorin cores and coordination of the central zinc ion with the 3 1 ‐hydroxy or 3 1 ‐methoxy group of a neighboring molecule, leading to the formation of slipped‐stack structures with J ‐type excitonic coupling .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DSC, as a suitable dye sensitizer, exhibits a promising photovoltaic potential, and features a carboxy group at the C3 2 position on the chlorin macrocycle for covalent bonding with the TiO 2 nanocrystalline films. Some solution‐based DSSCs based on DSC have been investigated previously . In contrast, it has been observed that HTC‐1 and HTC‐2 show efficient charge transport with high mobilities owing to the combination of π–π stacking of the chlorin cores and coordination of the central zinc ion with the 3 1 ‐hydroxy or 3 1 ‐methoxy group of a neighboring molecule, leading to the formation of slipped‐stack structures with J ‐type excitonic coupling .…”
Section: Resultsmentioning
confidence: 99%
“…Chlorophylls (Chls), which are the most abundant natural pigments, play key roles in early photophysical and ‐chemical events in natural photosynthesis . In the last decade, we have carried out a series of investigations to explore the possibility of employing Chls and their derivatives in emerging photovoltaic techniques, such as biomimetic systems, DSSCs, organic solar cells (OSCs), and perovskite solar cells (PSCs) . These investigations are purely based on the fact that Chls are the only naturally occurring organic semiconductors that possess the merits of large‐scale resources, pollution free, and optoelectrical variability.…”
Section: Introductionmentioning
confidence: 99%
“…[141,143] For example, Hua et al reported two Ag-based metal organic complexes (HA1 ( Figure 15) and HA2) as dopant-free HTMs for CH 3 NH 3 PbI 3 PSCs. [141,143] For example, Hua et al reported two Ag-based metal organic complexes (HA1 ( Figure 15) and HA2) as dopant-free HTMs for CH 3 NH 3 PbI 3 PSCs.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The unique spectral properties of J and H aggregates are attracting increasing attention as regards practical implementation for solar energy . Here we have pointed out another possible important application of a JH aggregate as the prime absorbing medium of a luminescent solar concentrator.…”
Section: Discussionmentioning
confidence: 93%